Eco-innovation promoting the circular economy in Romania - Simona Frone (Revista română de economie, 2017)
The development of eco-innovation parks in our country may be a key to regional as well as national sustainable development, due to their special features and opportunities for industrial synergy. Implementing a circular and green economy is also a current important challenge to a systemic transformation agenda in the European Union. Therefore, a main objective of this paper is to analyse from the viewpoint of the circular economy principles (closing-the-loop in the resource management) the strategic role of eco innovation parks as a community of manufacturing and service enterprises seeking enhanced environmental and economic performance through collaboration in managing environmental and resource issues including energy, water, and materials. In this respect we analyse both the conceptual and practical importance of eco-innovation for the circular economy and point out the character of the industrial ecosystem, as a regional metabolism in fostering both eco-innovation and industrial synergy of the SMEs and organisations involved. The case studies and conclusions recommend the urge to identify, design and plan industrial ecosystems within an eco-innovation park as an important way promoting circular economy on regional, microeconomic and sectoral scale in Romania.
2665773-9; 2344-4657; Revista română de economie; 717197875